The birds of the republic of colombia: their distribution, and keys for their identification (1948)
In the autumn of the year 1938 the Academy of Natural Sciences of Philadelphia received in the post a section of bamboo inside of which was the skin of a flycatcher. It had been sent by Mr. Kjell von Sneidern, of Popayán, Colombia, as a sample of his work. As a result a trial lot of one hundred skins was ordered, and then another hundred, and from these small beginnings the Academy established long and very happy relations with Mr. von Sneidern, which resulted, during the following nine years, in the acquisition of 12 ,500 specimens from various regions in Colombia.